Moslem Family Education in The Digital Era - Samsudin, Mandasia; Sumardjoko, Bambang; Wildan, Muhammad; Maksum, Muh. Nur Rochim (Universitas Muhammadiyah Surakarta, 2023)
The quick improvement of computerized innovation today demonstrates that the world has entered another period known as the advanced time. In this computerized time, everybody can get to, give, convey, impart and take part in different web-based exercises. The universe of data innovation offers numerous comforts through mechanization, which benefits people in numerous ways. Nonetheless, this additionally makes expected misfortunes for people. Therefore, Muslim family education plays an important role in forming children who have noble character, are tough and wise, have a strong Islamic outlook, and are able to navigate and utilize technology effectively. Muslim family education is not just about providing information about religion, but also about creating an environment that supports the spiritual, moral and social growth of family members. Parents play an important role as role models in practicing Islamic values so that children can internalize the teachings in their lives. This article tries to offer a perspective on how Islamic family education prepares the Islamic generation in the digital era.